Effect of order of draw of blood samples during phlebotomy on routine biochemistry results. Issue 11 (21st July 2011) - Sulaiman, Raashda A; Cornes, Michael P; Whitehead, Simon J; Othonos, Nadia; Ford, Clare; Gama, Rousseau
Abstract : Aim: To investigate whether incorrect order of draw of blood samples during phlebotomy causes in vitro potassium ethylenediaminetetraacetic acid EDTA (kEDTA) contamination of blood samples. Methods: Serum kEDTA, potassium, calcium, magnesium, alkaline phosphatase, zinc and iron concentrations were measured in blood samples drawn before and after collecting blood into kEDTA containing sample tubes by an experienced phlebotomist using the Sarstedt Safety Monovette system. Results: EDTA was undetectable in all samples. The concentrations of other analytes were similar in blood samples drawn before and after collection of the EDTA blood sample. Conclusion: Order of draw of blood samples using the Sarstedt Safety Monovette system has no effect on serum biochemistry results, when samples are taken by an experienced phlebotomist.